2006
DOI: 10.1002/app.23998
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of polypropylene/low‐density polyethylene blends grafted with itaconic acid in the course of reactive extrusion

Abstract: This study was concerned with the structural features and mechanical properties of polypropylene (PP)/ low-density polyethylene (LDPE) blends, which after compounding were modified by the free-radical grafting of itaconic acid (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…This is in accordance with obtained morphology and mechanical properties. Krivoguz et al 33 showed that the PP/LDPE blends grafted with itaconic acid (IA) had the approaching values of T g , which allowed us to believe that in PP/LDPE-g-IA systems, interactions between PP and LDPE lead to partial mutual dissolution. particle size, especially in 80/20/7 blend.…”
Section: Dynamic Mechanical Analysismentioning
confidence: 99%
“…This is in accordance with obtained morphology and mechanical properties. Krivoguz et al 33 showed that the PP/LDPE blends grafted with itaconic acid (IA) had the approaching values of T g , which allowed us to believe that in PP/LDPE-g-IA systems, interactions between PP and LDPE lead to partial mutual dissolution. particle size, especially in 80/20/7 blend.…”
Section: Dynamic Mechanical Analysismentioning
confidence: 99%
“…The comparison of unfunctionalized starting polyolefins (LDPE and iPP) with runs LDPE_1 and iPP_1, and even with the functionalized blends, evidenced, as a general trend, that the LDPE phase crystallized more slowly ( T c decreased). This effect can be explained by the increase in LDPE melt viscosity during functionalization as revealed by the presence of crosslinked materials, mostly composed of the polyethylene fraction. By comparing the crystallization path of the samples functionalized by using MAH and peroxide in the same reagent ratio (R1 = 0.05, runs LDPE_1, iPP_1 and sample 5), we observed a decrease of T c associated with the iPP phase (or a phase iPP rich) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Krivoguz and Pesetskii extensively studied the grafting of itaconic acid by changing the LDPE/PP ratio: The rheological behaviour of the products evidenced once again the occurrence of degradation and crosslinking showing the two collateral reactions to be difficult to keep under control. The thermal and mechanical features of grafted LDPE/PP blends suggested the lack of compatibility at the level of crystalline phases, while efficient interactions on the amorphous fractions were highlighted as proved by the variation of the glass transition temperatures ( T g ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, technological equipment, particularly extrusion compounding reactors, has been updated continually, which should be taken into consideration in choosing optimal technological parameters for functionalization. Besides, the necessity of solving applied problems requires that basic research be done into functionalization of various olefin copolymers [1][2][3][4][5][6][7], polyethylene (PE) and polypropylene (PP) blends [8,9] as well as blends of polyolefins (PO) with copolymers of ethylene and higher olefins [10,11], copolymers of ethylene and vinyl acetate [12], linear polyethylene [13] and others. It should be noted that most studies of fundamental nature have been concerned with functionalization of PE and PP of conventional grades.…”
Section: Introductionmentioning
confidence: 99%